Modelling distributor performance in network marketing organisations - P. Msweli-Mbanga (South African Journal of Business Management, 2001)
This study develops a model that predicts distributor performance in network marketing organisations. Distributor performance is conceptually linked through formal hypotheses to perceptions of marketing mix, organisational commitment, job satisfaction and customer profile. Data was gathered from 500 network marketing distributors to test two nested models, one with job satisfaction as a determinant of performance, and the other with performance as a determinant of job satisfaction. The findings revealed that there was greater model parsimony when the causal direction of the performance/job satisfaction relationship was such that performance causes job satisfaction. The results support several of the a priori hypotheses and suggest that the perceptions of the marketing mix variable are not directly linked to performance, but that the relationship between the variables is mediated by the organisational commitment variable. Implications of the study to network marketing practitioners and avenues for further research are provided.
Keywords: 650